2013
DOI: 10.1188/13.onf.e101-e107
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Symptoms Following Surgery for Esophageal Cancer

Abstract: Patients with esophageal cancer are at risk for multiple prolonged symptoms following surgery. Symptom assessment should occur often after surgery and include a broad range of symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 20 publications
1
38
0
1
Order By: Relevance
“…Further details of the studies are given in Table 1. In general, all studies were considered deficient in one or more aspects of their study design/ reporting, which increased the likelihood of bias. In terms of selection, no eligibility criteria were reported in two studies [17,26], one prospective study used consecutive patients attending outpatient clinics [18] and all others used convenient samples from defined time periods [19][20][21][22][23][24][25][27][28][29][30][31][32][33]. Participation rate was reported in 16 of the 18 studies, and ranged between 66 and 100%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further details of the studies are given in Table 1. In general, all studies were considered deficient in one or more aspects of their study design/ reporting, which increased the likelihood of bias. In terms of selection, no eligibility criteria were reported in two studies [17,26], one prospective study used consecutive patients attending outpatient clinics [18] and all others used convenient samples from defined time periods [19][20][21][22][23][24][25][27][28][29][30][31][32][33]. Participation rate was reported in 16 of the 18 studies, and ranged between 66 and 100%.…”
Section: Resultsmentioning
confidence: 99%
“…No studies assessed the relationship between inadequacy of nutritional intake and change in nutritional status post-operatively. Table 4 summarises the six studies reporting change in nutritional status that also reported on nutrition related symptoms or quality of life [17,22,23,25,27,33]. Two of the studies employed a validated instrument in the assessment of patient reported outcomes [22,23].…”
Section: Changes In Dietary Intakementioning
confidence: 99%
See 1 more Smart Citation
“…Dysphagia is a very common mechanical cause of malnutrition and is accompanied by dietary changes in order to avoid foods that worsen symptoms leading to inadequate intake of calories. The surgical procedure often causes deficiencies in macronutrients and micronutrients, with the most prevailing side effects being postprandial dumping syndrome, dysphagia, anorexia, reflux, and early satiety [53][54][55]. Furthermore, chemotherapy affects rapidly proliferating cells preferentially and, consequently, affects the cells of the gastrointestinal tract.…”
Section: Mechanisms Of Malnutritionmentioning
confidence: 99%
“…Table 7 summarizes the studies reporting on the most common patient symptoms after surgery. 4,11,42,[44][45][46][47][48][49][50][51][52][53] These indicate a high prevalence of gastrointestinal symptoms. In studies reporting at 12 months or more, symptoms were seen with the following frequency: dumping syndrome 15%-75% (median 46%), dysphagia 11%-38% (median 27%), early satiety 40%-90% (median 65%) and reflux symptoms 19%-61% (median 29%).…”
Section: Later Challenges Nutrition and Weightmentioning
confidence: 99%